(untitled) (The Research of Medical Science Review, 2024)
Ischemic Heart Disease is a prevalent vascular condition of heart characterized by the development of atherosclerotic plaque within the vessel lumen. To evaluate clinical decision- making by comparing the long-term outcomes, safety, and effectiveness of CABG with PCI in patients with symptomatic multi-vessel coronary disease. This Cross-sectional study was conducted at Chaudhry Pervaiz Elahi Institute Of Cardiology Wazirabad during July to December 2023. Convenient sampling technique was used in this study. Data was collected with the help of Performa and by conducting a general history of the present condition of the patient after the fluoroscopic procedure (PCI) and surgical procedure (CABG), who came with complaints of MVCAD. Performa included questions about the history, presenting complaints, risk factors, information about obstructed vessels and their treatment decisions, ejection fraction, complications during the procedure, and outcomes after the procedure. The majority of the patients with symptomatic multi-vessel coronary artery disease were under the age of 75 (55.58%). The majority of patients with MVCAD were males 99(75.6%). Most of the patients presented complaints of central chest pain 34(26.0%). The most common complaint was central chest pain, observed in 26%. Additionally 22.9% presented with chest pain accompanied by SOB, while 13% reported chest pain radiating to both arms, shoulders, and back. Chest pain radiating with SOB was reported by 18.3%, and 11.5 presented with chest pain along with other symptoms. In conclusion, the comparison between coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in patients with symptomatic multivessel coronary disease reveals equivalent improvement in angina symptoms after 4 months.